Survei Program Kegiatan Mitigasi Bencana di Lembaga PAUD - Rohmatul Laili; Mallevi Agustin Ningrum (LP. Ma'arif Janggan Magetan, 2023)
Mitigation is a stage that aims to reduce the possibility of negative impacts when a disaster occurs. With disaster mitigation education, it is hoped that the public can understand the threat of disasters that will occur. How high is the level of achievement of disaster mitigation activity programs in PAUD institutions in West Surabaya, District. Benowo. The type of research used in this research is a quantitative survey with a descriptive approach. Data collection in this research took the form of a questionnaire in the form of a Google form. The results of data analysis used a one-sample t-test with right-hand hypothesis testing. Cronbach's Alpha value is Reliability, it is known that Cronbach's Alpha value is 0.874. This value is then compared with the R-Table value, with the N100 value searched for in the distribution of R-Table values ​​at a significance of 5%, an R-Table value of 0.180 is obtained. All variables have valid status because the calculated r-value (corrected Item-Total Correlation) r-table is 0.180. This disaster mitigation activity program can be used as a learning activity program, especially storytelling activities to help children understand disaster events. By providing play activities, children will feel happy and enthusiastic about participating in learning activities.